(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The use of virtual reality (VR) technologies in physical therapy is a promising area that overcomes the limitations of traditional treatment methods. This review article analyzes the interaction of different types of virtual reality (immersive, semi-immersive, and non-immersive), their impact on improving the rehabilitation process and effectiveness in physical therapy. The problem of the study is the lack of motivation of patients and their low level of involvement in traditional rehabilitation methods. The use of virtual reality is an innovative approach, but its comprehensive application requires a detailed analysis to determine the benefits and opportunities for integration into clinical practice. The purpose of the article is to summarize current research on the use of virtual reality in physical therapy, evaluate their effectiveness and identify the most promising areas of application. The method used for the analysis is a descriptive review, which includes peer-reviewed articles, clinical trials, and meta-analyses. The results of the review indicate that the combination of virtual reality with traditional methods helps to improve the motor functions, balance, and cognitive abilities of patients, which significantly improves the quality of rehabilitation. The novelty of the article lies in the analysis of the integrated use of these technologies, which allows overcoming the limitations of traditional therapy and ensuring more active participation of the patient in their own treatment. The practical significance of the study lies in the possibility of applying the findings by medical professionals and physical therapists to introduce new approaches to patient rehabilitation.